Laparoscopic myomectomy-The gold standard - Anja Herrmann; Rudy Leon De Wilde (Wolters Kluwer Medknow Publications, 2014)
Uterine myomas are the main cause for gynecological disease in premenopausal women. If a myomectomy is indicated, abdominal myomectomy is still a frequently performed procedure although laparoscopic myomectomy should be the method of choice. Searches were conducted in PubMed and The Cochrane Library to identify relevant literature. Compared with myomectomy by laparotomy and minilaparotomy, laparoscopic myomectomy is associated with improved short-term outcomes. Laparoscopy is further associated with less adhesion formation. Pregnancy rates after myomectomy in symptomatic patients might be higher after laparoscopy than after laparotomy. Although uterine ruptures following laparoscopic myomectomy are described in the literature, it seems to be a rare event. Concerning the recurrence, there is evidence that rates are similar after laparoscopy and laparotomy. Myomectomy by laparoscopy has several advantages over abdominal myomectomy (by conventional laparotomy and minilaparotomy) and should be the standard procedure. Despite the advantages of laparoscopy, abdominal myomectomy is still a frequently performed procedure. Lack of training in advanced laparoscopic procedures hampers the widespread use of laparoscopic myomectomy. Due to the advantages of laparoscopic surgery, efforts should be made to implement this procedure into daily practice. To provide the best care, physicians should offer patients the opportunity of a laparoscopic treatment of myomas.